Honokiol Ameliorates Post-Myocardial Infarction Heart Failure Through Ucp3-Mediated Reactive Oxygen Species Inhibition - Liu, Jianyu; Tang, Minghai; Li, Tao; Su, Zhengying; Zhu, Zejiang; Dou, Caixia; Liu, Yan; Pei, Heying; Yang, Jianhong; Ye, Haoyu; Chen, Lijuan (Frontiers in Pharmacology, 2022)
Post-myocardial infarction heart failure (post-MI HF) is one of the leading global causes of death, and current prevention and treatment methods still cannot avoid the increasing incidence. Honokiol (HK) has previously been reported to improve myocardial ischemia/reperfusion injury and reverse myocardial hypertrophy by activating Sirt1 and Sirt3. We suspect that HK may also have a therapeutic effect on post-MI HF. In this study, we aimed to investigate the efficacy and mechanism of HK in the treatment of post-MI HF. We found that HK inhibited myocardial ROS production, reduced myocardial fibrosis, and improved cardiac function in mice after MI. HK also reduced the abnormality of mitochondrial membrane potential (MMP) and apoptosis of cardiomyocytes caused by peroxide in neonatal cardiomyocytes. RNAseq results revealed that HK restored the transcriptome changes to a certain extent, and significantly enhanced the expression of mitochondrial inner membrane uncoupling protein isoform 3 (Ucp3), a protein that inhibits the production of mitochondrial ROS, protects cardiomyocytes, and relieves heart failure after MI. In cardiomyocytes with impaired Ucp3 expression, HK cannot protect against damage caused by peroxide. More importantly, in Ucp3 knockout mice, HK did not change the increase in ROS level and cardiac function damage after MI. Taken together, our results suggest that HK can increase the expression of the cardioprotective protein Ucp3, maintain MMP, thereby inhibiting the production of ROS after MI and ameliorating HF.